Tinea pedis in dermatological patients in the own study - Kamińska-Winciorek, Grażyna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2005)
There are difficulties in eradication of tinea pedis because of often asymptomatic carrier state, unconscious infection, easy to reinfection and long-term period of spore life in shoes and socks. In summertime 2000-2002 clinical tests on hospitalized patients of Dermatological Department of Silesian Medical Academy in Katowice were done. Diagnostic tests to detect of mycotic infection were performed on the basis of the methods which are used in Mycological Department of Dermatological Department of Silesian Medical Academy in Katowice. The number of sampled men in selected group was 43 patients of Dermatological Department. The study included history taking with filling in the questionnaire during samples taking and the mycologic tests after dermatological examination. After proved skin and nail changes (interdigital spaces, soles) scrapings samples were taken. In all cases mycologic cultures in Sabouraud medium were performed. In 43 patients’ group nobody notified any skin lesions or a mycotic infection and typical dermatological changes in the disease course. Skin changes on the foot were observed in 16 (37.2%) examined men, including mycotic infections in 9 (20.9%) men. The most frequent clinical type of mycotic infection was interdigital, intertiginous form of tinea pedis. In most cases, dermatophytes from skin lesions were isolated, but participation of yeast was common. Mycotic changes were localized mostly in interdigital spaces. To sum up, tinea pedis in patients of Dermatological Department of Silesian Medical Academy was 20.9%. In the etiology of tinea pedis, proved by clinical morphology and mycological examination, dermatophytes were the most frequent factor.